2023
DOI: 10.1021/acs.energyfuels.3c00303
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Promotes High Dispersion of V2O5 on 3D Porous g-C3N4 Carrier to Enhance Catalytic Oxidative Desulfurization Performance

Abstract: In this work, a series of supported catalysts V 2 O 5 / 3D g-C 3 N 4 were prepared by a solvothermal method and programmed calcination, where a vanadium-based ionic liquid (V-IL) [(C 8 H 17 ) 3 NCH 3 ] 3 H 3 V 10 O 28 was used as the vanadium source and 3D porous carbon nitride (3D g-C 3 N 4 ) acted as the carrier. The detailed structural and compositional characterization results show that the use of V-IL promotes the high dispersion of V 2 O 5 on the carrier and effectively avoids the problem of agglomeratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…By conducting free radical trap tests to determine the catalytic active intermediates during the reaction. Normally, p -benzoquinone (BQ) and dimethyl sulfoxide (DMSO) are applied as scavengers to trap superoxide radicals (O 2 · – ) and hydroxyl radicals ( · OH), respectively. As shown in Figure a, the catalytic activity is slightly affected after adding BQ into the reaction system. However, when DMSO is added, the desulfurization efficiency is completely inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…By conducting free radical trap tests to determine the catalytic active intermediates during the reaction. Normally, p -benzoquinone (BQ) and dimethyl sulfoxide (DMSO) are applied as scavengers to trap superoxide radicals (O 2 · – ) and hydroxyl radicals ( · OH), respectively. As shown in Figure a, the catalytic activity is slightly affected after adding BQ into the reaction system. However, when DMSO is added, the desulfurization efficiency is completely inhibited.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the activity of the catalysts was influenced by factors such as the surface area, titania dispersion, and Ti loading. However, increasing the Ti loading to more than 50% resulted in a decrease in the number of surface-active Ti species, which may have led to a decline in catalytic activity. ,, Antanse-phased TiO 2 has received significant attention for its photocatalytic ability to remove S compounds as a result of its chemical stability, non-toxicity, and high adsorptive property . Shen et al conducted a study using TiO 2 nanoparticles as an amphiphilic catalyst and increased the loading amount from 1.27 to 9.85 wt %.…”
Section: Influence Of Reaction Factors On Odsmentioning
confidence: 99%
“…However, pure HPAs generally have poor thermal stability and are easily soluble in polar solvents, making them difficult to recover and reuse when used as catalysts . In view of the characteristics of ionic liquids (ILs) and the widespread application as catalysts, if HPAs are combined with organic cations to form new HPA-based ionic liquid catalysts, they would be able to solve the above problems while retaining excellent catalytic performance of HPAs. …”
mentioning
confidence: 99%